Redes sociais (social networks) de deslocados/as pelo conflito sírio no Brasil: a solidão como articuladora de experiências migratórias - Silva, Juliana Carneiro da (2023)
This study analyzes the relationship between forced displacement and social networks in the context of people displaced by the Syrian conflict in Brazil. The field study was performed intermittently between 2018 and 2022 using participant observation, informal conversations and semi-structured interviews, initially in the city of São Bernardo do Campo; with the pandemic of COVID-19, and the resulting shift from field study to the digital environment, the study included people displaced by the Syrian conflict living in other Brazilian cities as well. Mediation occurred mainly through an online course of Portuguese for migrants where I taught as a voluntary teacher in 2020 and 2021. Here, the social networks are assessed under several perspectives – practical support, family relationships, marriage arrangements, sociability, and emotional support – that reveal that loneliness traverses all aspects of the participants’ lives. Thus, I argue that loneliness, although not an all-encompassing feeling, articulates the experiences of these migrants amid the forced displacement and the forging of their lives in Brazil, to the extent that not only it is produced within these several aspects, but also indicates the relationship between them: sometimes loneliness produced in one aspect increases the loneliness created in another (as happens in the relation with the State in face of the public policies of reception and the creation of networks where they can get practical support), sometimes it is expected that some parts of life can alleviate loneliness and absences felt in other parts (marriage is seen by some participants as such an event since it is invested of potential to offer moments of sociability, sources of practical and emotional support and/or job opportunities, something that Zbeidy (2020b) has pointed out in her studies in Jordan). I also show that, although articulating those migrant experiences, the loneliness I have found in the field is not homogeneous, being present in several ways in their lives